Desafíos pedagógicos ante el uso de las Tecnologías de la Información y la Comunicación en la Educación Superior del Ecuador - Mayorga Albán, Amalín Ladaysé (2014)
The vision of the use of Information and Communications Technology (ICT) has changed; ICT is now conceived as a tool to access knowledge, by including it in the curricula at all levels of education. It is important to highlight the role of the teacher in this process. Some teachers acknowledge ICT as an object for knowledge. Others see ICT as didactic tools for teaching. Proper use of ICT leads to the development of science and shows itself as a pedagogical challenge at incorporating ICT into the classroom as an object for knowledge and study, as a virtual scenario for teaching and learning and as a tool to strengthen meta-cognitive skills. Technology is increasingly subject to the challenges teachers have to face when imparting learning. Higher education is no exception, and at this level it is present through the use of platforms, programs and tools used both by teachers and students. The weakness or absence of use of ICT for learning in all forms has been determined as one the 19 main problems of the Academic System in Ecuador